2024
DOI: 10.3748/wjg.v30.i13.1815
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into clinical trials for immune checkpoint inhibitors in colorectal cancer: Unravelling challenges and future directions

Samantha Sharma,
Naresh Singh,
Anita Ahmed Turk
et al.

Abstract: Colorectal cancer (CRC) is a complex disease with diverse etiologies and clinical outcomes. Despite considerable progress in development of CRC therapeutics, challenges remain regarding the diagnosis and management of advanced stage metastatic CRC (mCRC). In particular, the five-year survival rate is very low since mCRC is currently rarely curable. Over the past decade, cancer treatment has significantly improved with the introduction of cancer immunotherapies, specifically immune checkpoint inhibitors. Therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 206 publications
(216 reference statements)
0
2
0
Order By: Relevance
“…Over the years, significant advancements have been made in the field of CRC therapeutics, resulting in improved survival rates attributed to progress in both primary and adjuvant treatment methods[ 2 ]. Notably, the integration of chemotherapy as either a neoadjuvant or adjuvant intervention has emerged as a strategic approach to mitigating tumor burden, reducing its size, and stabilizing its growth[ 3 ].…”
Section: To the Editormentioning
confidence: 99%
“…Over the years, significant advancements have been made in the field of CRC therapeutics, resulting in improved survival rates attributed to progress in both primary and adjuvant treatment methods[ 2 ]. Notably, the integration of chemotherapy as either a neoadjuvant or adjuvant intervention has emerged as a strategic approach to mitigating tumor burden, reducing its size, and stabilizing its growth[ 3 ].…”
Section: To the Editormentioning
confidence: 99%
“…Immunotherapy has become a promising treatment for cancer alongside radiotherapy, achieving significant clinical efficacy. Preclinical studies have demonstrated that immunological approaches, such as immune checkpoint inhibitors (ICIs) and cancer vaccines, can produce effective antitumor responses ( 1 , 2 ). Additionally, immune checkpoint drugs are currently undergoing clinical trials, yielding encouraging results with reduced adverse reactions.…”
Section: Introductionmentioning
confidence: 99%